From Portable to SCA Raman devices to characterize harmful compounds contained in used black slag produced in Electric Arc Furnace of steel industry. (13th July 2013) - Gómez‐Nubla, Leticia; Aramendia, Julene; de, Silvia Fdez‐Ortiz; Castro, Kepa; Madariaga, Juan Manuel
<x xml:space="preserve">Abstract</x> Black slag from steel production is an industrial waste used as secondary material for some applications (forest tracks, cement, etc.). When it disposed to the open air, little is known about possible side effects that could appear with time. To foresee those side effects, various Raman equipments were used. This analytical strategy has been applied to six different black slag. Four of them were obtained from two steel producers (two original and two with treatment of 'inerting'), and the other two sampled in civil construction works, which supposedly should be treated. Results showed the original mineral phases of the samples (iron and other metal oxides, silicates, ferrites…) and the new phases (calcite, natron, nitratine, goethite, limonite, ilesite, etc.) resulting from the superficial reaction with the atmospheric acid compounds. This fact indicates a strong reactivity between slag and surrounding environment where they have been deposited. Only with one of the three setups, all the compounds could not be detected: (1) the handheld spectrometer detected the major ones and few of the minor ones, (2) the laboratory Raman microprobe ascertained nearly all of the compounds, but cannot be translated to the field and (3) Structural and Chemical Analyser (SCA), which combines micro‐Raman spectroscopy and Scanning Electron Microscopy/ Energy Dispersive X‐Ray Spectroscopy (SEM‐EDS) on the same spot, recognized the trace compounds, which were the most harmful ones. These results demonstrate the greater applicability of this new strategy in comparison with traditional methods for the chemical characterization of black slag and its alteration products. Copyright © 2013 John Wiley & Sons, Ltd.